Analysis of Effective Management Strategy and Competence in Improving Team Productivity and Performance in the IT Sector Industry - Prabantarikso, R. Mahelan (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the relationship between management strategy, individual competence, productivity, and team performance. The research method used is a quantitative descriptive approach with data collection through questionnaires to employees in the information technology sector totaling 753 employees. The analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM). Reliability and validity are tested using Composite Reliability (CR), Cronbach's Alpha, and Average Variance Extracted (AVE). The results of the study indicate that effective management strategies and individual competence have a positive influence on increasing team productivity and performance. The conclusion of this study confirms that the implementation of the right management strategy, combined with the development of individual competence, plays an important role in increasing team productivity and performance.